An Analysis of the Effectiveness of the Tax Volunteer Program in Improving Administrative Efficiency and Taxpayer Compliance at KPP Pratama Situbondo - Ahmad Fathoni; Aditya Lutfi Sadewa; Aminatus Zahriyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Indonesia's stagnant tax ratio and declining taxpayer compliance have become major challenges to financing national development, particularly in regencies characterized by agrarian-coastal economies and low levels of tax literacy. This study aims to analyze the effectiveness of the Tax Volunteer Program in improving tax administration efficiency and individual taxpayer compliance at the Situbondo Primary Tax Office (KPP Pratama Situbondo). A comparative quantitative descriptive approach was employed using primary data collected through questionnaires administered to 50 individual taxpayers during the final week of the 2025 Annual Tax Return (SPT) filing period, complemented by direct observations throughout the tax assistance process. Secondary data were obtained from the Directorate General of Taxes' Annual Reports for 2024–2025. The findings reveal a substantial improvement following the increase in the number of tax volunteers from four in 2024 to thirteen in 2025. The number of taxpayers served increased from 1,564 to 4,490, representing a 287% increase. Service efficiency was maintained within an average processing time of 5–9 minutes despite the transition to the Coretax system. Taxpayer satisfaction was notably high, with 88% reporting being very satisfied and 12% satisfied with the services provided. The study also identified improvements in taxpayers' understanding of tax obligations, increasing from 65% to 79%, while the adoption rate of the e-Filing system reached 95.5%. Theoretically, these findings support the Slippery Slope Framework and the Theory of Planned Behavior, demonstrating that tax volunteers play a significant role in fostering taxpayer trust and strengthening perceived behavioral control. The study concludes that the Tax Volunteer Program is effective in enhancing tax administration efficiency and taxpayer compliance in regency-level jurisdictions and has the potential to serve as a replicable model for similar regions across Indonesia.